2012
DOI: 10.1038/pr.2012.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light exposure on metalloporphyrin-treated newborn mice

Abstract: Background: Neonatal hyperbilirubinemia arises from increased bilirubin production and decreased bilirubin elimination. Although phototherapy safely and effectively reduces bilirubin levels, recent evidence shows that it has adverse effects. Therefore, alternative treatments are warranted. Metalloporphyrins, competitive inhibitors of heme oxygenase (hO), the rate-limiting enzyme in bilirubin production, effectively reduce bilirubin formation; however, many are photoreactive. here, we investigated possible phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Bilirubin and biliverdin failed to induce SPIC-EGFP in Spic igfp/igfp BMDM (Figure 2D). Furthermore, iron chelation by deferoxamine or HO1 inhibition by chromium mesoporphyrin (Crmp) (Schulz et al, 2012b) failed to inhibit heme-mediated SPIC-EGFP induction (Figures S4B and S4C). These results argue against a role of heme metabolites in Spic induction.…”
Section: Resultsmentioning
confidence: 99%
“…Bilirubin and biliverdin failed to induce SPIC-EGFP in Spic igfp/igfp BMDM (Figure 2D). Furthermore, iron chelation by deferoxamine or HO1 inhibition by chromium mesoporphyrin (Crmp) (Schulz et al, 2012b) failed to inhibit heme-mediated SPIC-EGFP induction (Figures S4B and S4C). These results argue against a role of heme metabolites in Spic induction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, treated infants showed a photosensitivity when phototherapy was applied (10). In addition, we have found that zinc deuteroporphyrin bis-glycol (ZnBG) and chromium mesoporphyrin (CrMP) have photo-and chemical toxicity, respectively, despite both being highly potent (26). And, except in two healthy adult studies showing no oral absorbance of SnPP (27) and SnMP (28), all the Mps tested in earlier trials have been administered parenterally (i.v.…”
Section: Articlesmentioning
confidence: 99%
“…In a recent publication (31), we demonstrated the possible photosensitising effects of two promising Mps for use in the prevention of neonatal jaundice, CrMP and ZnBG. We chose these two compounds because both are orally absorbed, relatively potent with minimal photoreactivity in the desirable dose range and minimally upregulates HO-1 transcription.…”
Section: Effect Of Light Exposure On Metalloporphyrin-treated Newbornmentioning
confidence: 98%
“…HO activity was calculated as pmol CO/h/mg fresh weight (FW) and then expressed as mean ± SD% of control values. To evaluate toxicity, pups were treated similarly and then immediately placed for 3 h under fluorescent tubes (2 cool white/1 blue TL52) to test for phototoxicity or kept in the dark to test for chemical toxicity . Overall survival of pups was then monitored up to 1 week.…”
Section: Evaluation Of the Znpp Formulationsmentioning
confidence: 99%
See 1 more Smart Citation